Pengaruh Ion Logam Cd(II) Terhadap Ekstraksi Ion Timbal(II) Menggunakan Teknik Emulsi Membran Cair - Rizka Setyani; Baharuddin Hamzah; Suherman Suherman (Jurnal Akademika Kimia, 2016)
This study aims to study on the effect the addition of Cd (II) metal ions towards extraction of lead (II) ions using liquid emulsion membrane technique. Various concentrations of Cd (II) ions used in this study were 0, 50, 100, 150, 200, and 250 ppm. Benzoyl acetone was used as a chelating agent for extraction. Spectrophotometer spectrodirect was used to measure extraction products. The results showed that percent extraction of lead (II) ion prior additional Cd(II) ion was 99.06%, and it was decreased up to 97.95% after additional Cd(II) ion up to 250 ppm.